Milenar Resistencia and Reexistence: History and Struggle in the Poem A noite nao adormece nos olhos das mulheres, by Conceicao Evaristo - Braz, Pedro Henrique [UNESP]; Coqueiro, Wilma dos Santos [UNESP]; Silva, Sandro Adriano da [UNESP] (Univ Federal Espirito Santo, 2020)
Conceicao Evaristo's poetic production emphasizes a black female lyrical self that gives voice to an ancestral corporeality. Thus, the author conquers the speech place and the identity emancipation of the black woman, silenced by prejudices and stereotypes that have historically emerged in Brazilian society, reverberating for centuries in an exclusionary and elitist literary canon. Corroborating the subversion of this cultural structure, Poemas da Recordacao e Outros Movimentos (2017) presents a lyrical voice that expresses different racial-ethnic demands, especially of some marks of black feminism. From these elements, the objective here is an interpretative analysis of the poem A noite nao adormece nos olhos das mulheres, which integrates the mentioned book, investing in the relations between the poetic configurations and the social themes that make it possible to glimpse the poem a subjective position regarding historical memory and the reflections of a lyrical self, assumed in its identity and ancestry.
Keywords: Afro-brazilian literature; Poetry; Conceicao Evaristo